Biomechanical Comparison of Three Internal Fixation Techniques for Stabilizing Posterior Pelvic Ring Disruption: A 3D Finite Element Analysis - Hu, Pan (Orthop Surg, 2019)
OBJECTIVE: To compare the biomechanical stability and compatibility of two iliosacral screws (ISS), a tension band plate (TBP), and a minimally invasive adjustable plate (MIAP) for treating Tile C pelvic fractures. METHODS: Three groups of finite element models of the intact pelvis, including the main ligament and the proximal one‐third of both femurs, were developed to simulate vertical sacral fractures and treated with the three abovementioned internal fixation techniques. A 500 N vertical load, a 500 N vertical load plus a 10 Nm moment of forward sagittal direction, and 500 N vertical load plus a 10 Nm moment of right lateral direction were applied to the sacrum to simulate standing status, bending status, and flexion status, respectively. The maximum displacement value, the stress value, and the stress value of the fracture interface were compared among the three internal fixation techniques. RESULTS: The results showed that all three internal fixation techniques effectively restored the biomechanical transmission of the injured pelvis. The stress on the implants in the TBP model was 167.47% and 53.41% higher than that in the ISS model and the MIAP model, respectively, and the stress shielding phenomenon of the TBP model was more obvious than in the other two models. Meanwhile, the stress between the fracture interfaces in the TBP fixation models was apparently higher than that in the other two models. However, the vertical displacement of the MIAP model was not significantly different from that in the ISS and TBP model; therefore, strong fixation could be obtained in all three models. CONCLUSION: Based on our results, we believe that the stability of Tile C pelvic fracture fixed with MIAP was similar to that of fractures fixed with ISS and TBP, but the stress shielding phenomenon and safety of implants in the TBP models were inferior to those in the MIAP and ISS fixation models. Meanwhile, MIAP and ISS fixation were more helpful to the healing processing than was TBP fixation, especially at the fracture interface of the second and third vertebral body levels.